The Effect of Carbon Emission Disclosure, Environmental Performance, and Firm Size on Profitability - Priscilia Christie Lee; Rousilita Suhendah (Jurnal Akuntansi, Keuangan, dan Manajemen, 2026)
Purpose: This study examines the effects of carbon emissions disclosure, environmental performance, and firm size on profitability. Research Methodology: Nineteen companies were selected as samples using purposive sampling. The study used secondary data sourced from the annual reports and sustainability reports of each company and analyzed using a multiple linear regression approach with a fixed-effects model using Microsoft Excel and EViews 12 software. Results: The results of the research analysis indicate that carbon emission disclosure has a negative effect, environmental performance has no significant effect, while firm size has a positive effect on profitability in Indonesian mining companies. Conclusions: Regression analysis shows that carbon emissions disclosure (X1) has a negative effect, environmental performance (X2) has no significant effect, and firm size (X3) has a positive effect on profitability. Limitations: This study is limited to three independent variables, an observation period of 2021–2023, and a focus on the mining sector; therefore, the results cannot be generalized to other sectors. Contributions: This research is expected to benefit companies in making strategic decisions related to sustainability, investors in evaluating financial and non-financial performance, academics in enriching the literature on factors that influence profitability, and further researchers in expanding the variables, sectors, and research periods.